Long-term prognosis and risk factors in tricuspid valve replacement surgery: a single-center study - Ke, Yingjie; Hua, Linbin; Pang, Shanwen; Wang, Qiuji; Zhong, Lishan; Wang, Zhenzhong; Zhou, Kan; Zeng, Rong; Huang, Huanlei (Frontiers in Surgery, 2025)
BackgroundTricuspid valve replacement (TVR), although accounting for a minority of heart valve surgeries, poses significant challenges, including poor patients’ condition, prosthetic complications, and increased perioperative mortality rates. Despite preferences for valvuloplasty, some cases necessitate replacement. The choice of tricuspid valve type remains controversial, and there is no consensus on surgical risk factors. Additionally, long-term follow-up reports on a large number of cases are lacking. In this study, we aimed to analyze the medical records of the largest number of patients who underwent TVR surgery.MethodsPatients who underwent TVR between 1999 and 2023 were divided into mechanical (MTVR) and bioprosthetic (BTVR) groups. Risk factors for overall mortality were analyzed.ResultsIn total, 626 patients were enrolled. The in-hospital and overall mortality rates were 12.1% and 42.8%, respectively. The in-hospital mortality rate (7.0% vs. 14.2%), incidence of acute renal insufficiency (4.3% vs. 12.2%), and hemodialysis rate (3.2% vs. 10.4%) were significantly higher in the BTVR group than in the MTVR group (P < 0.01). The median follow-up was 11 years (range 0.1–24 years). The MTVR group had significantly higher rates of long-term survival, hemorrhagic events, heart failure events, and re-operation rates than the BTVR group (P < 0.01). Multifactorial logistic regression analysis identified body weight, New York heart function classification, extracorporeal circulation time, and ventilator time as independent risk factors for in-hospital mortality. New York heart function classification during follow-up was identified as an independent risk factor for overall patient mortality.ConclusionsMTVR was superior to BTVR regarding short- and long-term outcomes. New York heart function classification was associated with short- and long-term mortality.